Some issues of legal regulation of the media sphere of the Republic of Kazakhstan (Herald of Journalism, 2019)
In this article the author considers the latest scientific and philosophical concepts of the problem of consciousness. In this regard some issues related to the legal regulation of electronic media in the network information society were analyzed. Mass media services are carried out in the field of social theories as a tool for obtaining and disseminating information developing a society namely forming an information society. The purpose of the article is to provide mechanisms for forecasting the capabilities and prospects of the media in the context of legal regulation in developing a development strategy for the information society of Kazakhstan today. Analysis of factors contributing to the formation and development of the Kazakhstan media space and the information society in interaction with the global media space.Along with empirical methods such as description, control and comparison, theoretical axiomatic approaches to the analysis, systematization and sociometric approach to the materials of foreign scien-tists are applied to the analysis of the research topic.The main result of the scientific article is the description of the model of the information society the identification of the problems of adapting the old norms governing the media to new requirements. To search for an algorithm for creating the information society in the sustainable use of information technol-ogy an analysis of world experience is carried out in connection with which the study vector is aimed at substantiating the scientific concept of the importance of regulating social media in the formation and development of the model of the Kazakhstan information society.
Keywords: Information society, social media, convergent journalism,normative-legal system.